Sea‐level scenarios for evaluating coastal impacts. (3rd October 2013) - Nicholls, Robert J.; Hanson, Susan E.; Lowe, Jason A.; Warrick, Richard A.; Lu, Xianfu; Long, Antony J.
Abstract : Global‐mean sea‐level rise will drive impacts and adaptation needs around the world's coasts over the 21st century and beyond. A key element in assessing these issues is the development of scenarios (or plausible futures) of local relative sea‐level rise to support impact assessment and adaptation planning. This requires combining a number of different but uncertain components of sea level which can be linked to climatic and non‐climatic (i.e., uplift/subsidence of coastal land) factors. A major concern remains about the possibility of significant contributions from the major Greenland and Antarctic ice sheets and this must be factored into the assessments, despite the uncertainty. This paper reviews the different mechanisms which contribute to sea‐level change and considers a methodology for combining the available data to create relative (or local) sea‐level rise scenarios suitable for impact and adaptation assessments across a range of sophistication of analysis. The methods that are developed are pragmatic and consider the different needs of impact assessment, adaptation planning, and long‐term decision making. This includes the requirements of strategic decision makers who rightly focus on low probability but high consequence changes and their consequences. Hence plausible high end sea‐level rise scenarios beyond the conventional Intergovernmental Panel on Climate Change (IPCC) range and which take into account evidence beyond that from the current generation of climate models are developed and their application discussed. Continued review and development of sea‐level scenarios is recommended, starting with assimilating the insights of the forthcoming IPCC AR5 assessment. WIREs Clim Change 2014, 5:129–150. doi: 10.1002/wcc.253 This article is categorized under: Assessing Impacts of Climate Change > Scenario Development and Application